Legal Observations on the Enslavement of the Native and Foreign Born in the Ancient Near East in the Second and Early First Millennium B.C. - Ziskind, Jonathan R. (1969)
legal discrimination in favor of the native born who are enslaved either at home or in foreign countries: Lev. 25; LE § 52; CH § 280 f.; MAL § 2 f.; CHitt. § 19В.